Fluorescence Commutation and Surface Photopatterning with Porphyrin Tetradithienylethene Switches. Issue 7 (27th December 2017) - Biellmann, Thomas; Galanti, Agostino; Boixel, Julien; Wytko, Jennifer A.; Guerchais, Véronique; Samorì, Paolo; Weiss, Jean
Abstract: Four tetradithienylethene (DTE) substituted porphyrins, the free base1H2, and three metal derivatives (1Zn, 1Co, 1Ni ), were synthesized and studied. These dyads, for which the DTE units are connected to the porphyrin's meso positions via a meta ‐phenyl spacer, exhibit reversible photochromic properties in all cases, with conversion to the photostationary state (PSS) up to 88 %, as confirmed by absorption and NMR spectroscopies. Compounds 1H2 and1Zn are fluorescent in solution and display a red emission. Upon irradiation with UV light to trigger the closing of the DTEs, the fluorescence of both the free base and zinc porphyrin was very efficiently quenched in solution. The reversible, photo‐switching of luminescence was retained in a tetra‐DTE free‐base porphyrin‐doped polystyrene film, for which photo‐patterning was demonstrated by confocal scanning microscopy. The tunable fluorescent properties of this multi‐DTE framework render this compound of interest as a photo‐rewritable fluorescent ink. Abstract : Think pink ink : Multiple switching events of dithienylethenes around a porphyrin core provide highly contrasted fluorescence readout and photo‐rewritable fluorescent inks.